Effect of transcutaneous auricular vagus nerve stimulation on postoperative liver function in patients undergoing partial hepatectomy: a study protocol for a prospective, double-blind, randomized controlled trial - Yuanyuan Wang; Yuanyuan Wang; Zhengxiu Sun; Zhengxiu Sun; Yongao Lin; Yongao Lin; Mingshu Tao; Mingshu Tao; Wenxin Zhao; Wenxin Zhao; Jinling Liu; Jinling Liu; et al. (Frontiers in Medicine)
BackgroundPartial hepatectomy remains a primary therapeutic intervention for various hepatic diseases. However, several intraoperative factors, including surgical manipulation, substantial blood loss, the need for blood transfusions, and hypoxic stress, can significantly impair liver function. Current perioperative strategies aimed at protecting the liver exhibit certain limitations. Transcutaneous auricular vagus nerve stimulation (taVNS), an emerging non-invasive neuromodulation technique, has demonstrated potential in preserving organ function through vagus nerve-mediated anti-inflammatory mechanisms. This study is designed to evaluate the hepatoprotective effects of taVNS on liver function in patients undergoing elective partial hepatectomy under general anesthesia.Methods/designIn this single-center, prospective, double-blind, randomized controlled trial, 140 patients scheduled for partial hepatectomy will be randomly allocated in a 1:1 ratio to either the transcutaneous auricular active-taVNS or sham taVNS groups. Both groups will receive 60-min stimulation sessions at four predefined time points: (1) at the onset of the first hepatic portal occlusion, (2) post-extubation, (3) on postoperative day 1 (6:00–7:00 a.m.), and (4) on postoperative day 2 (6:00–7:00 a.m.). The primary outcome is alanine aminotransferase (ALT) level measured in venous blood samples collected at 7:00 a.m. on postoperative day 2. Secondary outcomes include postoperative levels of inflammatory markers, renal function indicators, quality of recovery, gastrointestinal function recovery, pain, fatigue, anxiety, incidence of postoperative delirium, and time to first flatus, bowel movement, and oral intake, all of which will be assessed using validated instruments.DiscussionPostoperative liver function dysfunction following partial hepatectomy remains a significant clinical complication that negatively impacts patient prognosis and long-term survival outcomes. TaVNS, an emerging non-invasive neuromodulation technique, has demonstrated considerable potential for perioperative organ protection in preclinical studies. This study aims to provide robust evidence regarding the therapeutic efficacy of taVNS in reducing hepatic injury after partial hepatectomy. By introducing a novel approach to perioperative hepatic protection, taVNS may contribute valuable insights into the development of multimodal hepatoprotective strategies.